Can the nucleic acid amplification test (NAT) be an alternative to the serologic tests? A prospective study, the results of 18,200 blood donors from the Turkish Red Crescent - YÜKSEL MAYDA, PELİN; Kosan, Erdogan; Kocazeybek, Bekir; Altunay, Husnu; Aymelek, Meryem; Alan, Esra; Saribas, Suat; Aslan, Mustafa; Yenen, Osman Sadi; Yuksel, PELİN; Birinci, Ilhan; Kirali, Kaan; et al. (My University, 2010)
Aim: Serologic tests having high sensitivity and specificity are used in order to prevent contamination with infectious agents from blood and blood products for transfusion safety. The present serologic tests have problems such as low sensitivity and weak detection capacity of infectious agents in the -window period-. We aimed to test the use of NAT (Nucleic Acid Amplification Test) in routine blood screening in the Blood Bank.